Pengaruh Budaya Organisasi dan Gaya Kepemimpinan terhadap Motivasi Kerja Anggota Organisas Remaja Masjid Melati Muda di Suryowijayan, DIY - Puja Rukmana; Amalia Aswin Fannisa; Bangun Putra Prasetya (STIKes Ibnu Sina Ajibarang, 2025)
This quantitative study seeks to ascertain the impact of organizational culture and leadership style on the work motivation of the “Melati Muda” mosque youth group in Suryowijayan, Yogyakarta. The research had 46 active participants chosen through purposive sampling. Data were gathered via questionnaires employing a Likert scale. “The data were examined with multiple linear regression through IBM SPSS Statistics 26. The t-test results indicated that leadership style has a considerable impact on work motivation, although organizational culture does not have a meaningful partial influence. The F-test demonstrates that both factors collectively exert a considerable influence on work motivation. The Adjusted R Square value of 0.215 signifies that the independent variables account for 21.5% of the variance in work motivation, whilst the remaining 78.5% is affected by factors not analyzed in this study. These findings underscore the significance of proficient leadership in augmenting motivation within faith-based youth groups.